Internet-based questionnaire to self-assess autonomy and obtain a life-at-home services enforcement plan: a retrospective validation study. (July 2015) - Koskas, P; Scemama, E; Wolfowicz, B
Background: In France, a specially-designed care plan for the elderly is generally based on an interdisciplinary, complex and time-consuming process. The health system assigns care throughout the social and health care services using multiple providers and sites. Objective: The free websitewww.jesuisautonome.fr offers senior citizens and their families an opportunity to assess their own independence at home using a questionnaire in order to obtain a personal, life-at-home, enforcement plan. We aim to examine the correlation between the specially-designed care plan obtained by the usual assessment method and through self-evaluation via the website. Methods: Community-dwelling subjects, consulting for the first time from December 2012 to July 2014, were under consideration. Patients were assessed using the Comprehensive Geriatric Assessment (CGA) and also independently during the first consultation; patients and their caregivers were then asked to fill out the questionnaire on the website. The two methods were compared using the Bland-Altman analysis for quantitative values and Kappa values for qualitative values. Results: 73 patients completed the study. Correlation was excellent between parameters that did not include error due to risk to the patient (assistance with bathing and dressing, a nurse for drug distribution, measure of legal protection). Correlation was good with housekeeper hours that involved a financial cost to state social services and families. The GIR (Iso Ressource Groupe), which in France serves as a reference to determine social disability of the elderly, was similar. Conclusion: Our study confirms the potential of the websitewww.jesuisautonome.fr . to improve the delivery of health and social care services.